2015
DOI: 10.1515/hf-2015-0073
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of cubic oak specimens from the Vasa ship and recent wood by means of quasi-static loading and resonance ultrasound spectroscopy (RUS)

Abstract: The cylindrical orthotropy, inherent timedependency response, and variation between and within samples make the stiffness characterisation of wood more challenging than most other structural materials. The purpose of the present study is to compare static loading with resonant ultrasound spectroscopy (RUS) and to investigate how to combine the advantages of each of these two methods to improve the estimation of the full set of elastic parameters of a unique sample. The behavior of wood as an orthotropic mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
(35 reference statements)
0
12
0
Order By: Relevance
“…In particular, this will allow the definition of an error function to be minimized during the inversion process. Scanning Laser Vibrometer (SLDV), and/or holographic techniques, can be used to experimentally determine the sample modes shapes (Vorobyev et al 2016). In this paper, it is proposed to use the following steps for the identification:…”
Section: Inverse Identification Of the Elastic Constantsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, this will allow the definition of an error function to be minimized during the inversion process. Scanning Laser Vibrometer (SLDV), and/or holographic techniques, can be used to experimentally determine the sample modes shapes (Vorobyev et al 2016). In this paper, it is proposed to use the following steps for the identification:…”
Section: Inverse Identification Of the Elastic Constantsmentioning
confidence: 99%
“…Ideally, using only one sample is preferable and allows studying the natural variability. In this context, quasi-static measurements on a single sample of wood have been taken (Bruno and Poggialini 2005;Bruno et al 2008;Majano-Majano et al 2012;Seichepine 1980;Vorobyev et al 2016). This method can be accurate for determining the Young's moduli and some of the Poisson's ratios, but is not so suitable for the determination of the shear moduli on a heterogenous material like wood, due mainly to a non-homogeneous stress field, and it is time-consuming (Hassel et al 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased macroscopic stiffness upon impregnation with PEG has been reported previously by Bjurhager et al (2010). A recent study by Vorobyev et al (2016) investigated the combined effect of aging and impregnation of PEG in Vasa oak on the macroscopic elastic properties as compared with the case of recent oak and found that all Young's moduli and shear moduli along the principal material axes were lower for the Vasa material. For wood with comparable densities and microfibril angles, cell wall softening correlates with an associated softening of the wood on the macroscopic scale (e.g., Gibson et al 2010).…”
Section: Influence Of Peg Treatment On Mechanical Properties Of Oak Cmentioning
confidence: 57%
“…This procedure aimed at replacing the water in the wood cell walls by PEG and thus preventing shrinkage and formation of cracks during drying (Håfors 2001). Since salt precipitation on numerous surfaces on the ship had been reported (Sandström et al 2002), a series of investigations of the chemistry (Glastrup et al 2006;Almkvist and Persson 2008a, b;Lindfors et al 2008;Almkvist et al 2016) and also of the mechanical properties of Vasa oak wood (Ljungdahl 2006;Bjurhager et al 2012;Vorobyev et al 2016) have been performed over the last years. These research activities showed that the oak wood is affected by degradation, i.e., by depolymerization of polysaccharides.…”
Section: Introductionmentioning
confidence: 99%